Combining virtual learning environment and integrated development environment to enhance e-learning - Fetaji, Majlinda; Loshkovska, Suzana; Fetaji, Bekim; Ebibi, Mirlinda (IEEE, 2007)
The research was undertaken having in consideration two hypothesis. The first hypothesis is that integration of virtual learning environment (VLE) and integrated developing environment (IDE) for programming in Java language will contribute in improving the efficiency and quality in learning because of the enhanced graphical user interface and the “hands on approach”. 7KHVHFRQGK\SRWKHVLVLVWKDWWKHGHVLJQHG graphical user interface of the virtual learning environment will contribute in facilitating its use by improving the results of the learning process, increasing the user-satisfaction and attention during learning that implicates improving the overal efficiency of learning programming in Java. The aim of this paper was to discuss difficulties and disadvantages of learning programming in traditional method, and to investigate for new e-learning strategies by combining e-learning and developing environment whereas the importance of the pedagogical approach is discussed and one is adopted in the design. The usability of the created virtual environment was reviewed, in order to assess and propose solutions to the identified issues.
Keywords: Development environment, virtual environment, e-learning, enhanced learning